2015
DOI: 10.3324/haematol.2014.115170
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Ataxia Telangiectasia Mutated-null phenotype in chronic lymphocytic leukemia with pro-oxidants

Abstract: © F e r r a t a S t o r t i F o u n d a t i o n(ROS) production or reduced antioxidant capacity. A principle antioxidant pathway is regulated by the redox sensitive transcription factor, NF-E2 p45-related factor-2 (NRF2/NFE2L2). In unstressed cells, low levels of NRF2 are maintained through interaction with Kelch-like ECHassociated protein 1 (KEAP1), an adapter for the E3 ubiquitin ligase Cullin 3 (CUL3) that directs NRF2 for proteasomal degradation. 13 Modification of redox and electrophile sensitive cysteine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…This in turn can induce DNA fragmentation as previously reported. 36,55 It has been demonstrated that the USP7 inhibitor P5019 also inhibits USP47 with a comparable EC 50 to USP7. 56 Although the potential off-target effects of HBX19818 have not been thoroughly tested, in this study we demonstrate that many of the cellular phenotypes resulting from USP7 inhibition with HBX19818 can be recapitulated by knocking down USP7 with siRNA.…”
Section: Discussionmentioning
confidence: 99%
“…This in turn can induce DNA fragmentation as previously reported. 36,55 It has been demonstrated that the USP7 inhibitor P5019 also inhibits USP47 with a comparable EC 50 to USP7. 56 Although the potential off-target effects of HBX19818 have not been thoroughly tested, in this study we demonstrate that many of the cellular phenotypes resulting from USP7 inhibition with HBX19818 can be recapitulated by knocking down USP7 with siRNA.…”
Section: Discussionmentioning
confidence: 99%
“… 6 PTL ( 1 ) demonstrates effective and selective anti-CLL activity in vitro , 7 and through its pro-oxidant activity, can target CLL cells independently of their p53 status. 8 Furthermore, co-authors of this report 9 are among those who have shown that ATM-deficiency disrupts redox homeostasis, increasing further the sensitivity of this DDR-defective subtype of CLL to PTL. 10 In addition to inducing oxidative stress, PTL has been shown to target tumour cells by suppressing pro-survival and proliferation signalling through the NF-κB pathway, 11 by inhibiting JAK–STAT kinase activity and thereby preventing STAT-mediated transcription of anti-apoptotic genes and by inhibiting DNMT1 and HDACs leading to activation of epigenetically silenced tumour suppressor genes.…”
Section: Introductionmentioning
confidence: 88%
“…16 u PTL has been shown to induce oxidative stress in cancer cells, 17 and recently DMAPT ( 2a ) was confirmed to induce oxidative stress in CLL cells. 9 There are a number of reports on the use and derivatisation of PTL, with a view to addressing various cancer types, 16z , 18 but the only PTL derivative to be applied to CLL remains compound 2a . 19 Previous studies have used molecular docking to investigate 1 and 2a which have suggested that interaction with IKKβ is a plausible mechanism for their action against haematological and solid tumours.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, our results suggest that ATM and AIF are functionally related in a positive feedback loop in which they regulate each other in neuroblastoma cells following Ad.5/3- CTV infection (Fig 7). Another recent study reported that treatment with pro-oxidant resulted in caspase-independent, AIF-dependent apoptosis in ATM-null primary CLL tumors (50). These results from others and us suggest that ATM and AIF can work independently or together to induce caspase-independent cell death.…”
Section: Discussionmentioning
confidence: 99%